2002
DOI: 10.1590/s0100-06832002000400009
|View full text |Cite
|
Sign up to set email alerts
|

Fósforo da biomassa microbiana e atividade de fosfatase ácida após aplicação de fosfato em solo no sistema plantio direto

Abstract: A atividade de fosfatases e a biomassa microbiana são fundamentais no ciclo do fósforo no solo e no seu fornecimento às plantas. Este trabalho analisa os reflexos da aplicação de fósforo na atividade de fosfatase ácida e no acúmulo de fósforo na biomassa microbiana em solo no sistema plantio direto. Em janeiro de 2000, coletaram-se amostras da camada de 0-10 cm nos tratamentos de doses acumuladas de 0, 130, 180, 260, 360, 540, 720, 980 e 1.240 kg ha-1 de P2O5 em seis anos de cultivo de um experimento em Latoss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
20
0
26

Year Published

2010
2010
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(59 citation statements)
references
References 23 publications
13
20
0
26
Order By: Relevance
“…These results have evidenced that soil management has a strong impact on microbial P incorporation. The lower microbial C:P ratio under the coffee canopy and the higher ratio in the inter row space confirmed previous observation that microbial C:P ratios depended strongly on the P status of the soil (Saffigna et al, 1989;Guerra et al 1995;Conte et al, 2002). Under the coffee canopy, the average available P content was around 3.5 times higher than that in the inter row space.…”
Section: Microbial Biomass Ratiosupporting
confidence: 88%
“…These results have evidenced that soil management has a strong impact on microbial P incorporation. The lower microbial C:P ratio under the coffee canopy and the higher ratio in the inter row space confirmed previous observation that microbial C:P ratios depended strongly on the P status of the soil (Saffigna et al, 1989;Guerra et al 1995;Conte et al, 2002). Under the coffee canopy, the average available P content was around 3.5 times higher than that in the inter row space.…”
Section: Microbial Biomass Ratiosupporting
confidence: 88%
“…Phosphate fertilisation increases soil P concentrations and may, therefore, decrease soil phosphatase activity (Tabatabai, 1994). Similar results were reported by Carneiro et al (2004) for the Cerrado and Conte et al (2002) for the South of Brazil. However, crop rotation studies in Ponta Grossa, Parana, Brazil, produced high acid phosphatase values, ranging from 799.1 to 489.9 µg PNP g -1 h -1 .…”
Section: Resultssupporting
confidence: 89%
“…Conte et al (2002) found that this enzyme activity was not influenced by higher P availability in the soil. However, in this study, in P3 under irrigation, greater phosphatase activity was stimulated, reaching higher levels than the other forms of P splitting in both soil layers.…”
Section: Microbiological Propertiesmentioning
confidence: 80%
“…The microorganisms absorb and immobilize P in the soil solution, when the availability is higher in the soilplant system, but gradually release P by adjusting the microbial population to the energy and P supply in the system (Conte et al, 2002;Martinazzo et al, 2007). This may have occurred in this study; the available P in the soil solution may have been immobilized and at this stage (three years and four months after soil P application), this nutrient may have been released gradually through increased phosphatase enzyme activity, as well as the higher MBC concentration, bearing in mind that, for this same P dose (1,800 kg ha -1 ), MBC was also higher than in the other P treatments in the 5-10 cm layer.…”
Section: Microbiological Propertiesmentioning
confidence: 99%